Rural Community-Based Tourism Development in Bangladesh: The Conceptual Issues - Afjal Hossain, Md; ., Uchinlayen (International Journal of Engineering and Technology, 2018)
The concept of rural tourism can revitalize the conventional concepts of tourism, and bring socio-economic and environmental well-being of the rural community ensuring sustainable development of a particular country. The aim of this paper is to identify the prospects and problems of rural community-based tourism development in Bangladesh. Rural tourism is one of the most promising tourism sectors in Bangladesh. It can bring economic, social and environmental benefits to the community people. Development of the rural tourism will have a significant impact on the GDP and employment opportunities for them who are involved in its development process. This paper finds out some barriers of rural community-based tourism development and provides some suggestions to overcome those challenges. For the development of this promising sector, it needs proper policy formation, infrastructure development, human resource development, enough investment for services and facilities in the destination areas, readiness of rural people to arrange tourism in their areas, public private partnership, sustainable tourism development guidelines, etc. Finally, this paper also looks into at how rural community people of Bangladesh can be involved in the development of tourism activities in their own areas.)Â Â